Modeling of suitable sites for creation of nature reserves in Halabja province using fuzzy logic method. - Mustafa, Dr.Rebaz Luqman Mustafa (Sulaimani Journal for Humanities, 2025)
This research is entitled (Sampling of suitable places for the creation of nature reserves in Halabja province using fuzzy logic method), nature reserves are considered one of the most important areas, which play a major role in environmental protection and survival of wildlife They have a unique ecology. The main objective of the study is to draw a scenario for identifying the most suitable places for the creation of nature reserves in Halabja province, which analyzed the natural and human criteria of the province using fuzzy logic methods The research stems from the fact that Halabja province is rich in natural and human resources and attractive landscapes and is able to create a nature reserve to become an attractive tourist area and protect the environment and nature The study showed that the research area area (295.32 km2) is very suitable for the creation of nature reserves, which accounted for 28.59% of the total study area The category (unsuitable) accounted for 21.99 km2 and 2.13%. Keywords: prototyping, suitable location, nature reserve, Halabja province, Fuzzy Logic method.
Keywords: Modeling; suitable location; nature reserve; Halabja province; Fuzzy Logic method